Effects of water table on cellulose and lignin degradation of Carex cinerascens in a large seasonal floodplain. Issue 1 (1st January 2018) - Zhang, Guangshuai; Yu, Xiubo; Gao, Yang; Li, Ya; Zhang, Quanjun; Liu, Yu; Rao, Didi; Lin, Yongming; Xia, Shaoxia
ABSTRACT: Water table affects litter decomposition in wetlands, but its effects on the degradation of cellulose and lignin are poorly understood. We performed a decomposition experiment in Poyang Lake Wetland, to determine how water table affected the degradation of cellulose and lignin. After 60 days of decomposition at a site with a relatively highly water table, 46.19% of initial cellulose and 41.95% of initial lignin remained. Decay rates of both cellulose and lignin increased as the depth of the water table increased. Principle component analysis showed that the decay rates of cellulose and lignin increased with increasing soil pH, but decreased with increasing contents of clay and fungi: bacteria ratio. The path model accounted for 66% and 79% of the variation in cellulose and lignin decay rates, respectively, and considered the effects of interactions between the water table and related factors. The cellulose decay rate was affected by the water table with a direct coefficient of 0.47, and an indirect coefficient of 0.65, but the lignin decay rate was indirectly affected by water table (coefficient, 1.25) and directly affected by soil property (coefficient, 0.67). Thus, the water table affected the decomposition of cellulose and lignin via different mechanisms.